Dilema Pasal 88 UNCLOS 1982: Antara Tujuan Damai dan Mobilisasi Militer di Laut Lepas - Nabil Zaidan Hermawan (Jurnal Ilmiah Penegakan Hukum, 2026)
This article aims to analyze the normative ambiguity of Article 88 UNCLOS 1982 concerning "peaceful purposes" on the high seas, particularly when confronted with modern military technology advancements. The problem focuses on the absence of an operational definition of "peaceful purposes" capable of distinguishing military navigation freedom (Article 87) from the threat of force prohibited by Article 2(4) of the UN Charter. The research gap is that the classic debate between Oxman (restrictive) and Francioni (permissive) both ignore contemporary technological realities, where even the passive presence of a combat fleet can create a coercive effect. To approach this problem, a normative legal method is used with statutory, conceptual, and case approaches. Primary legal materials are analyzed qualitatively through grammatical, systematic, and teleological interpretations. The novelty of this research is the proposal of a robust interpretation of Article 88, which prohibits not only open aggression but also offensive military mobilization that creates a latent threat. This study concludes that the presence of stealth nuclear submarines and long-range cruise missiles on the high seas has blurred the boundary between passive activity and active threat, thus Article 88 must be interpreted robustly. Recommendations include the need for multilateral negotiations to formulate interpretative Guidelines under ITLOS and strengthening the due regard obligation.